Obtaining a Flexible Film Elaborated from Cassava Thermoplastic Starch and Polylactic Acid - Germán A. Arboleda; Camilo E. Montilla; Héctor S. Villada; Giovanni A. Varona (International Journal of Polymer Science)
A flexible film was obtained from a blend of cassava thermoplastic starch and polylactic acid, using maleic anhydride as coupling agent. For this, an experimental design with three factors was used: polylactic acid content, coupling agent content, and temperature profile of the blown extrusion. It was found that the three factors generated significant differences on the response variables of tensile mechanical properties individually as in their triple interaction. Differential scanning calorimetry (DSC) was used by understanding the behavior of thermal properties of TPS/PLA blends with and without coupling agent, finding similar results between both. From this, the combination with 28% polylactic acid, 0.87% coupling agent, and 155.75°C temperature profile permitted the obtaining of a material with outstanding mechanical properties and offered advantages from the economic point of view.